Personal department controls of micro and small companies: an analysis of companies in the central region of Rio Grande do Sul (Research, Society and Development, 2020)
This research aimed to understand how internal control can help the personal department sector of micro-enterprises and small businesses in the central region of the state of Rio Grande do Sul. Descriptive research was used to carry out this study as an objective, adopting a qualitative approach and using technical procedures related to a survey based on a selected sample. Through a questionnaire, we sought to analyze the practices, the structure of the PD and the understanding of the owners of the companies located in the urban area of the studied municipality, with a total of nineteen participants. The results indicated the existence of few defined personal departments, but regarding the perception of entrepreneurs regarding the use, scope and adaptation of internal controls for the personal department, presented a favorable result. Internal control helps ME and PPS to be preventively protected from risks related to the company's business, because with this control organizations have better performances and satisfactory results, facilitating their survival in the market.